RANCANG BANGUN SISTEM PENAHAN PANAS PADA MOTOR ROKET CIGARETTE BURNING - Sutrisno (BRIN Publishing, 2006)
The thrust of cigarette burning rocket motor is relatively lower but the is burning time is too long than that of the radial burning. The cigarette burning rocket motor structure easy to be fail due to the thermal stress thermal effect. Hence the thermal insulation sistem becomes very important. This paper discuss about the design and preparation of thermal insulation system in the cigarette burning rocket motor. The carbon and polyester fiber were used as the thermal protector materials in burning chamber. The liner matrix and inhibitor in the cap side were made from epoxy. O-ring spacer was applied to avoid the gas leakage from the combustion chamber. The performance of thermal insulation system was tested through static test of rocket motor. The result of the test provide that thermal insulation system showed the good performance. It is found that the burning time of the rocket motor is 116 second and the maximum temperature of the outer surface of the tube is 139 degree celcius.